Livelihoods sustainability: Malaysia's experience and its implication for cooperation with West Asia - Abdulai, Abdul-Mumin; Siwar, Chamhuri (IKRAB, UKM, 2010)
This chapter examines Malaysia's livelihoods sustainability success story and the extent to which such success could be used to cement cooperation with West Asian countries. The prospects and challenges have been investigated by this chapter, and suggestions offered to enhance such development cooperation